2003
DOI: 10.1093/aob/mcg072
|View full text |Cite
|
Sign up to set email alerts
|

Application of Architectural Analysis and AMAPmod Methodology to Study Dwarfing Phenomenon: the Branch Structure of 'Royal Gala' Apple Grafted on Dwarfing and Non-dwarfing Rootstock/Interstock Combinations

Abstract: Architectural analysis was applied to study branch development of 'Royal Gala' apple trees grafted with dwarfing and non-dwarfing rootstock/interstock combinations, which had been chosen to produce trees with a wide range of vigour. Using AMAPmod methodology, the structure of 3-year-old branches was described at four levels of representation: branch; annual shoot; growth unit; and node. Three types of growth units were distinguished: extension growth unit (vegetative unit with internode extension); vegetative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 14 publications
5
37
1
Order By: Relevance
“…The TD is used to calculate the trunk cross-sectional area (TCSA), both values testifying to the strength of the tree growth. The TCSA in apple 'Royal Gala' is significantly affected by rootstock and/or interstock (Seleznyova et al, 2003), the finding being in conformity with the results of the present study for the second season, though, when the effect of BA 29 on TD was facilitated and that of MA diminished most likely by a factor that was not controlled in the trial.…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 91%
See 1 more Smart Citation
“…The TD is used to calculate the trunk cross-sectional area (TCSA), both values testifying to the strength of the tree growth. The TCSA in apple 'Royal Gala' is significantly affected by rootstock and/or interstock (Seleznyova et al, 2003), the finding being in conformity with the results of the present study for the second season, though, when the effect of BA 29 on TD was facilitated and that of MA diminished most likely by a factor that was not controlled in the trial.…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 91%
“…Nevertheless, pear is usually considered as a vigorous species and its branching habit is often naturally erect. Dwarfing rootstocks are commonly used to reduce more rapidly the vigour of the pear trees, and consequently to promote earlier flowering (Seleznyova et al, 2003). However, the present study showed that the trees which developed fewer sylleptic shoots in the first years of growth were not the best solution to obtain an entrance into the productive period in the second and third year.…”
Section: Analysis Of Syllepsis Intensitycontrasting
confidence: 70%
“…Due to a high level of heterozigosity, each tree represented a unique genotype which strongly affects fruiting behaviour of the tree and, consequently, morphometric traits of the shoots. Our results revealed a genetically determined plan of the annual shoots development, which is, according to Seleznyova et al (2003), one of the primary aims of the architectural analysis in general.…”
Section: Discussionmentioning
confidence: 67%
“…Despite their utility and a century of research, the underlying mechanism of rootstock-induced dwarfing is still unknown. The effects of dwarfing rootstocks are apparent within the first year after grafting and include reduced root growth, 1–3 a decrease in the length and node number of the primary axis, 4–6 a decrease in the number and length of sylleptic shoots 7,8 and/or an increase in the proportion of floral buds along the primary axis. 8–10 …”
Section: Introductionmentioning
confidence: 99%